Essential elements at play in local environmental policy change: A guide for the perplexed. Issue 106 (April 2020) - Pivo, Gary; Henry, Adam Douglas; Berger, Lena
Highlights: Empirical studies report three types of factors linked to local policy change: governance, environment and innovation design. Most factors are common to multiple theories; change agency and social context are common to all. Other factors shared by nearly all theories are power, organizational capacity and natural environmental conditions. Two theories – the Advocacy Coalition Framework and the Multilevel Perspective – include the most factors studied. Convergence is apparent in the empirical and theoretical work, giving us a holistic understanding of how local change occurs. Abstract: Rapidly evolving environmental problems in urban areas require new policy directions. However, the policy change process can be hard to comprehend, making it difficult to foster needed change. In this paper, a systematic review of international empirical research on sustainable urban water policy is used to identify key factors shaping local policy innovation. Those factors are then compared to leading theories of the policy process or technology change in order to place the results within a broader theoretical context. This article is meant to aid policy actors seeking to manage change, as well as students and scholars seeking an overview of this complex field. Thirty drivers of policy change are described and organized into a categorical framework under governance, environment or innovation design. Some drivers of change, such as household income or political orientation, are less easily altered by change agents than others, such as convening collaborations, exercising leadership and expanding organizational capacity. The comparison to policy theories suggests a convergence of theoretical and empirical literatures. Some drivers, like change agency and social context, are "theoretically ubiquitous, " by occurring in every theory, while others, like power, organizational capacity and natural conditions, are "theoretically prevalent, " by occurring in most. The Advocacy Coalition Framework and the Multilevel Perspective are theories which incorporate the most factors at play. They also share an interest in change being driven by social networks coalescing around shared beliefs in what is possible or desirable.